ABOUT THE LIMITATION OF USE OF THE COST APPROACH FOR PRICE FORMING IN HOUSING MARKET - Ivasiv, I. I.; Danyliuk, M. O. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
A number of technical and economic features affecting pricing in building production, determine the methods specifics for determining prices of construction products. In today's conditions of building market relations the most widespread is a cost approach to the prices formation in the residential real estate market, which, together with the significant advantages, has a number of shortcomings, which indicate the limited use of it, namely: the unreliability of reflecting the projected income value; the problem of calculating the cost of old buildings reproduction; the complexity of determining the value of accumulated old buildings depreciation; a separate assessment of the land plot from the buildings; the discrepancy between the cost of the acquisition of the estimated property object costs for the new construction of exactly the same object. The article deals with the processes of price policy formation at the building industry enterprises with the purpose of improving their competitiveness. The peculiarities of costly methods use of real estate valuation, their advantages and disadvantages are revealed. The main factors influencing formation of the pricing policy of building industry enterprises are analyzed. It is proved that a cost approach is appropriate to apply for new construction analysis, for the identification of various options for land use, for assessment for tax purposes, insurance, consequences of natural disasters and, if necessary, assessment of special buildings and structures.